Big Data Pada Smart City : Konsep dan Manfaat - Vhania Mutiara Sinaga (Madani: Jurnal Ilmiah Multidisiplin, 2023)
Smart cities emerge as demands for the development of cities that are livable, controlled and easily accessible. The purpose of this writing is to explain the concept and benefits of big data in implementing smart cities. Through a literature review, the smart city concept takes the form of city development and management by utilizing information and communication technology as a link, monitoring and controlling a city's resources effectively and efficiently. In addition, big data with the main characteristics of volume, velocity and variety is identified as a wealth of information that can improve decision making and overcome the challenges of data integration in the smart city concept. Thus, the importance of using big data in smart cities can be seen in solving environmental problems in city development. By understanding and knowing the concepts and benefits of big data in smart cities, a city government can adopt concepts and examples of the use of big data in smart city components in accordance with the culture and conditions of its people in order to improve city performance and make public services more feasible in realizing sustainable development.